Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-01-22T08:33:57+01:00
X-2y=4/*(-1)
x+3y=0

-x+2y=-4
x+3y=0

5y=-4
y=-0,8

x-2*(-0,8)=4
x+1,6=4
x=2,4
1 5 1
2010-01-22T08:57:12+01:00
X - 2y = 4/*(-1)
x + 3y = 0
.............dodajemy stronami
-x + 2y = -4
x + 3y = 0
5y = -4 /:5
y = -0,8
x - 2 * (-0,8) = 4
x + 1,6 = 4
x = 2.4
1 4 1
2010-01-22T10:22:48+01:00
X-2y=4
x+3y=0

x - 2y = 4 | * ( -1 )
x + 3y = 0

- 1x + 2y = - 4
1x + 3y = 0

( x nam się skracają ) +
--------------------------
(dodajemy)

5y = - 4 | : 5
y = -0, 8



x - 2y = 4
( za y podstawiamy -0, 8 )
x - 2 * ( - 0, 8 ) = 4
x + 1, 6 = 4
x = 4 - 1, 6
x = 2, 4

y = -0, 8
x = 2, 4